AB0449 Is Cost-Effective Treating to Target of Remission in Established Rheumatoid Arthritis? Results of the Create Registry. (9th June 2015) - Cárdenas, M.; de la Fuente, S.; Font-Ugalde, P.; Castro-Villegas, M.C.; Romero-Gόmez, M.; Ruiz-Vílchez, D.; Calvo-Gutiérrez, J.; Ortega-Castro, R.; Escudero-Contreras, A.; Casado, M.A.; Collantes, E.
Abstract : Background: Treating to target (T2T) of remission has proven to be the most efficacy strategy to achieve clinical remission in patients with early rheumatoid arthritis (RA), resulting cost-effective after three years. It involves monitoring disease activity, adjusting drugs to approved protocol and aiming at a predefined target. However there is not enough clinical evidence in established and persistent RA and it has not been established the target treatment strategy. Objectives: The objective was to estimate the cost-effectiveness of three strategies in real-life conditions from the Health Service perspective. T2T of remission versus achievement of low disease activity (LDA) and versus satisfactory disease control (SDC) after two years of treatment Methods: All patients diagnosed of RA according to the American College of Rheumatology who started biologic therapy between January 2007 and December 2012 were included in the Create registry. A multidisciplinary care team composed by rheumatologists, hospital pharmacists, nurse and statistical personal from a tertiary hospital was the responsible for making the decision about the treatment-choice. A T2T strategy aiming at remission (DAS28<2, 6) was applied to all patients. This included standardised and protocolised treatment adjustment. Patients were followed up and evaluated at least every two months. Measurements: Effectiveness was evaluated using the DAS28 value. Three different results were compared: Strategy 1 (S1): Clinical Remission (CR). DAS28<2, 6 at two years. Strategy 2 (S2): Patients at CR or at least with LDA (DAS28<3, 2) at two years. Strategy 3 (S3): Patients from S2 and also those patients with a DAS28>3, 2 at two years, but whose disease activity is judged by both the rheumatologist and patient to be low enough not to require switch of treatment (SDC). Care and cost: Direct health care costs were assessed from the hospital perspective and included the official drug acquisition costs, diagnostic tests, rheumatologist visits, hospital admission and use of day-care facilities for intravenous drug administration. Data were retrieved from hospital information system and electronic case reports forms. Data of two year follow-up were analysed. Cost-effectiveness: It was calculated dividing total direct healthcare mean costs by percentage of patients achieving the target clinical result for each strategy. Results: 144 patients were included. After two years, 32, 6% of patients achieved target for S1 (DAS28<2, 6), 57, 6% of patients reached at least DAS28 value<3, 2 (S2) and 90, 9% of patients reached a SDC (S3). Direct health mean cost after two years was 25, 976.05 € (IC95%:23, 888.16-28, 063.93). T2T of remission was the least cost-effective strategy: 79, 681.14€ per clinical remission (SD ±38, 880.43€), versus 45, 097€/LDA (±22, 00., 24€) and 28, 545.11€/SDC (±13, 958.59€), (p<0, 001 in both cases S1 vs S2 and S1 vs S3). Similarly, S2 was less cost-effective than S3 (p<0, 001). Conclusions: T2T of remission strategy with biologic therapy in established RA and in real-life conditions is less cost-effective than T2T of low disease activity or satisfactory disease control. Disclosure of Interest: None declared